2020
DOI: 10.1590/1413-785220202806237160
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade De Vida E Desafios De Familiares De Crianças Com Mielomeningocele

Abstract: RESUMO Objetivo: identificar os principais desafios da família de uma criança com Mielomeningocele (MMC) e correlacionar a escala de Zarit Burden Interview (ZBI) com o WHOQOL-BREF. Métodos: Foram enviados questionários via plataforma on-line para grupos de pais e cuidadores de crianças com MMC. Quatro dimensões foram avaliadas: física; psicológica; relações sociais; e meio ambiente do WHOQOL-BREF. Resultados: Todas as correlações entre os domínios do questionário WHOQOL-BREF com a escala de Zarit Burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
2
Order By: Relevance
“…Functional and clinical variables were not significantly associated with caregivers' burden. Other authors found that all correlations among caregivers'QoL and burden were negative (Buoro & Nogueira, 2020).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Functional and clinical variables were not significantly associated with caregivers' burden. Other authors found that all correlations among caregivers'QoL and burden were negative (Buoro & Nogueira, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Caregivers' burden and QoL of parents of children and adolescents with meningomyelocele have already been associated with patients' functional (Buoro & Nogueira, 2020; Cavalari et al, 2017) and clinical (Buoro & Nogueira, 2020; Valença et al, 2012) variables, caregivers' mental health and social impact (Rofail et al, 2012) and family income and composition (Buoro & Nogueira, 2020; Valença et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that most of the children have special needs, but there was no need to adapt the family home or car. Buoro and Nogueira 13 searched to identify the main challenges facing the family of a child with meningomyelocele. They observed that the quality of life of mothers and caregivers of children with meningomyelocele was affected regarding functional capacity, emotional aspects, and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Por isso é necessário tratar adequadamente e manter a saúde de uma criança com MMC, com acompanhamento contínuo com equipe multidisciplinar composta por pediatra, neurocirurgião, ortopedista, urologista, geneticista, nefrologista, fisioterapeuta, enfermeiro, psicólogo e trabalhador, que deve trabalhar de forma integrada, pois a criança precisa ser auxiliado em vários aspectos, para seu cotidiano seja digno sem muitas privações por parte da saúde tornando seu bem estar melhor com o autocuidado e desempenho de cada profissional. (Buoro & Nogueira, 2020).…”
Section: Segundo O Autorunclassified